PENGARUH BUDIDAYA LEBAH MADU TERHADAP PEREKONOMIAN MASYARAKAT DI KOTA PALANGKA RAYA - Amalina Putri Syahira; Muhammad Riza Hafizi; Hasnita Handayani (RAGAM: Journal of Statistics & Its Application, 2023)
The aim of this research is to determine the effect of honey bee cultivation on the economy of the people in Palangka Raya and from a Sharia Economic perspective. type of research causal research. The researcher's data collection method uses questionnaires. The population in this study were honey bee cultivation managers from the 3 (three) Forest Farmer Groups (KTH) supported by the Central Kalimantan Provincial Forestry Service, totaling 40 people, while the sample in this study was 40 people from all members of the population. The data analysis technique used is a simple linear regression analysis technique using the SPSS 25 program. The results of the research show that the honey bee cultivation variable has a significant positive effect on the community economy, which means that the higher the value of the honey bee cultivation variable, the higher the value of the community economic variable. Based on a sharia economic perspective, this is appropriate because honey bee cultivation managers have implemented the indicators that researchers use, such as social solidarity, transparency and trust.